2014
DOI: 10.2478/s11686-014-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

Grillotia erinaceus (van Beneden, 1858) (Cestoda:Trypanorhyncha) from whiting in the Black Sea, with observations on seasonality and host-parasite interrelationship

Abstract: The genus Grillotia Guiart, 1927 is cosmopolitan in its distribution and the type-species, G. erinaceus (van Beneden, 1858), has been relatively well studied. However, this study provides infection indices of Grillotia erinaceus from southern and northern Black Sea whiting Merlangius merlangus for the first time. The specimens of Grillotia erinaceus were obtained from subserosa of the anterior oesophagus, stomach, pyloric caeca, liver, ovaries and mesenterium of whiting caught by commercial fishing vessels off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…However S. pleuronectis has been previously reported in certain fish species in the same sampling region (Güneydağ et al 2017). Similarly, G. erinaceus has been reported in Merlangius merlangus in the same sampling area (Özer et al, 2014). Two cestodes species are reported in the scaldfish first time with this study.…”
Section: Discussionsupporting
confidence: 63%
“…However S. pleuronectis has been previously reported in certain fish species in the same sampling region (Güneydağ et al 2017). Similarly, G. erinaceus has been reported in Merlangius merlangus in the same sampling area (Özer et al, 2014). Two cestodes species are reported in the scaldfish first time with this study.…”
Section: Discussionsupporting
confidence: 63%
“…This species was described initially from species of Raja Linnaeus, 1758 from the coast of Belgium but was subsequently reported from various species of rays on both sides of the north Atlantic (Dollfus, 1942) and it was first reported with only morphometric data by Kornyushin & Solonchenko (1978) in a cartilaginous fish Raja clavata in the Black Sea. Later, Özer, Öztürk, Kornyushin, Kornyychuk, & Yurakhno (2014) provided detailed information about its seasonal and host related occurrence at two southern and northern locali- ties in the Black Sea. General features of the parasite are all in accordance with Kornyushin & Solonchenko (1978) and Beveridge & Campbell (2007) with some differences in measurement data of several parts of the scolex and tentaculate armatures as a result of possibly different environmental and host factors (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overall infection values determined in the present study were about 3 times higher in Sinop samples than that of Balaklava Bay samples, and the differences between localities were statistically signifi cant. Previous studies (see Table 1 for details) on H. aduncum infections in M. merlangus in Sinop coasts of the Black Sea reported high infection prevalence levels from 37.5 % to 100.0% and mean intensities from 3.8 to 12.8 per infected fi sh (Özer et al, 2000;Özer et al, 2009;Özer & Olguner, 2013;Tepe & Oğuz, 2013;Pekmezci et al, 2013). Skuratovskaya et al (2013) reported infection prevalence levels of H. aduncum ranging between 46 -65 % and 1 -12 per infected M. merlangus collected from Crimean coast of the Black Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Predatory fi sh, like gadoids, largely acquire and accumulate different stages of H. aduncum by ingesting crustaceans, chaetognaths and small fi sh species that are infected and serve as carriers (Klimpel et al, 2003;Klimpel & Rückert, 2005).Whiting is a commercially important fi sh species and widely distributed in the eastern North Atlantic Ocean, the northern Mediterranean, western Baltic and the Black Sea (ICES, 2006). It is particularly distributed along Romanian, Bulgarian, Turkish, Ukrainian, Russian and Caucasus coasts in the Black Sea (Burdak, 1960;Svetovidov, 1964;Gönener & Bilgin, 2010;Özer et al, 2014). The objective of the present study is to investigate the infection levels of H. aduncum in M. merlangus from the southern and northern Black Sea coasts and to provide fi rst detailed comparative ecological analysis of H. aduncum infection of whiting at both localities.…”
Section: Introductionmentioning
confidence: 99%